RESILIENSI SEBAGAI PENDUKUNG KESIAPAN ANAK MASUK SEKOLAH DASAR - Ria Novianti; Sabrina; Tri Umari; Titi Maemunaty; Aswandy Bahar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Children’s readiness to enter elementary school is a condition that parents and teachers should consider in early childhood education. The children’s school readiness has an impact on their social adjustment, interaction, and academic achievement. One of the essential aspects that children need to enter elementary school is resilience, or the ability to survive when they face problems and difficulties. This article provides a view on the readiness of children in entering formal education from the aspect of resilience. The review of resilience as the children’s readiness to enter formal education is interesting because nowadays, resilience is increasingly needed to fulfill children's readiness to enter formal education, considering the competition and pressures that children face in school. This article uses a literature review by collecting various references related to resilience and children’s school readiness to be discussed further. It is found that compassion, communication, empathy, and appropriate support provided by adults and schools with a conducive climate and fairness will foster and increase resilience in children. With good resilience, the child becomes tougher in facing the challenges they encountered in the school environment.